The effect of health education on personal hygiene on students' knowledge - Sinurat, Samfriati; Simanullang, Murni S D; Barus, Mardiati; Marbun, Gracia A (Trigin Institute, 2023)
Personal hygiene has a very important role in the growth and development of an elementary school child who is vulnerable to health problems. So that every student strives to maintain and carry out personal hygiene to maintain and carry out personal hygiene to prevent illness. So a student needs a good understanding of knowledge about good personal hygiene to be able to improve his health. One strategy to increase children's knowledge about personal hygiene is to provide health education. Health education is a learning process which means that in education there is a process of growth, development, or change towards a better and more mature individual, to change the behavior of the target from not knowing to knowing. The aim of this research is to determine the effect of health education on personal hygiene on the knowledge of students at SD HKBP Padang Bulan, Medan. The research design used was a pre-experimental design with a one-group pretest – posttest design, with a total of 64 respondents. The knowledge of HKBP Padang Bulan Elementary School students in Medan before being given health education with sufficient knowledge results as many as 34 respondents (53.1%) and after being given health education with good knowledge results as many as 64 respondents (100.00%). The results showed that there was an effect of health education on personal hygiene on the knowledge of SD HKBP Padang Bulan Medan students with a p-value of 0.000. The results of this study can be used as information for students of SD HKBP Padang Bulan Medan as the management of personal hygiene techniques to detect how clean hair, mouth & teeth and hands are.